Meningkatkan Kemampuan Teknik Dasar Sepak Bola Melalui Pendekatan Bermain terhadap Kelas VII SMP Negeri 1 Waru Sidoarjo - Galang Bakti Kurniawan; Nanik Indahwati; Demy Ilmiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research investigates the effectiveness of the play approach in improving basic soccer technical skills in class VII junior high school students. The main focus is on four key techniques: passing, controlling, dribbling and shooting the ball. This study uses Classroom Action Research (CAR) methodology which is carried out in two learning cycles. The research participants consisted of 39 students (19 boys, 20 girls) from SMP Negeri 1 Waru Sidoarjo. Data is collected through direct observation, skills tests, and documentation of the learning process. Analysis includes qualitative evaluation of student participation and quantitative assessment of skill scores. Results showed significant improvements in students' basic soccer technical skills. The average score increased from 74.05 in cycle I to 75.77 in cycle II. In addition, there was an increase in students' active involvement and the overall quality of the learning process. These findings indicate that the play approach is effective in improving basic soccer skills as well as students' learning motivation. This research provides valuable insight for sports educators about teaching strategies that can improve the learning of soccer techniques at the junior high school level.